Traditional risk factors and a Genetic Risk Score are associated with age of first acute coronary syndrome. Issue 20 (19th May 2014) - Labos, Christopher; Wang, Rui Hao Leo; Pilote, Louise; Bogaty, Peter; Brophy, James M; Engert, James C; Thanassoulis, George
Abstract : Objective: To examine the association between traditional risk factors (TRF) and a Genetic Risk Score (GRS) with age of first acute coronary syndrome (ACS). Early onset ACS may occur due to a high burden of TRFs or to genetic factors that accelerate atherosclerosis. Whether recently discovered genetic variants for ACS are more prevalent at earlier age of first ACS remains unknown. Methods: To construct a multilocus GRS, participants were genotyped for 30 single nucleotide polymorphisms (SNP) identified from prior genome-wide association studies. Linear regression models were fit to estimate the association between TRFs and GRS with age of first ACS. Results: We included 460 participants with a first ACS enrolled in the Recurrence and Inflammation in the Acute Coronary Syndromes (RISCA) cohort. Several TRFs were associated (all p<0.05) with earlier age of first ACS: male sex (6.9 years earlier (95% CI 4.1 to 9.7)), current cigarette smoking (8.1 years (95% CI 6.1 to 10.0)), overweight (Body Mass Index, BMI >25) and obesity (BMI>30) (5.2 years (95% CI 2.6 to 7.9)). In women, hormone replacement therapy was also associated with earlier age of first ACS (4.8 years earlier (95% CI 0.3 to 8.4)). After multivariable adjustment for TRFs, a 1 SD increment in the GRS was associated with a 1.0 (95% CI 0.1 to 2.0) year earlier age of first ACS. Conclusions: Among individuals with a first ACS, a GRS composed of 30 SNPs is associated with younger age of presentation. Although genetic predisposition modestly contributes to earlier ACS, a heavy burden of TRF is associated with markedly earlier ACS.